Global actors in Central Asia: Great Game or Great Gain? - Аубакир, Асима (Public Administration and Civil Service, 2020)
From the first days of their independence, the Central Asian states were constantly searching for the most optimal and beneficial ways to interact between each other and with other partners, both located in close proximity to their borders and relatively remote, but no less significant. The main goal and scientific novelty of this research is to analyze current approaches, taking into account the foreign policy doctrines of global actors (Russia, China, the USA and the EU) in relations with the countries of Central Asia. Particular attention is paid to the assessment and conclusions on the prospects for their development, including through the prism of the interests of the states of the region.